Body composition and determination of somatotype of the Spanish elite female futsal players - Castillo, M.; Sospedra, I.; González-Rodríguez, E.; Hurtado-Sánchez, J. A.; Lozano-Casanova, M.; Jiménez-Alfageme, R.; Martínez-Sanz, J. M. (Applied Sciences, 2022)
Background: In any sport, it is of the utmost importance to identify variables capable of positively influencing scores. Futsal is a sport of intermittent high-intensity intervals that requires the athletes` physical, technical, and tactical skills. There are no specific recommendations on anthropometry-body composition for this sport. The aim of this study was to describe the somatotype and the anthropometric characteristics, body composition, and somatotype of a group of Spanish elite female futsal players of the first-division league. Methods: Eighty-eight players (24 ± 4.94 years) from 14 teams of the first women`s division of the Spanish Futsal League were evaluated. Measurements were taken according to the anthropometric protocol of the International Society for the Advancement of Kinanthropometry (ISAK). Body composition (BC) and somatotype were calculated according to the 4-component model and Heath-Carter, respectively. Results: Pivot and goalkeeper positions were most different from the rest. Both were the heaviest positions and presented the largest mesomorphic data (4.13 ± 1.29 and 3.67 ± 0.95), kg of bone mass (10.60 ± 1.00 and 10.37 ± 1.08), and kg of lean mass (29.80 ± 1.25 and 29.12 ± 2.12), for the pivot and goalkeeper, respectively. Conclusion: The evaluation and evolution of the somatotype and BC is an assessment tool that could be a useful guide for technical and medical staff.